The Effect of Occupational Burnout Levels on Job Performance in Football Referees (8th Region Example) - Akif Bozkir; Mehmet Burak Demir (Journal of Educational Issues, 2024)
Football referees are responsible for the game order during the match, they must decide by quickly resolving the controversial positions. For this reason, it is very important to examine and discuss the facts to minimize the negativities in the decision-making factors of the referees. The aim of this study is to examine the effect of the level of occupational burnout suffered by football referees on job performance in the context of TFF 8th region referees. For this purpose, Maslach Burnout Inventory was used to determine the burnout levels of the participants and the job performance scale developed by Koca and Yıldız was used to measure their job performance. As a result, a significant negative relationship was found between the occupational burnout and job performance of football referees, which are the sub-dimensions of midlevel negative occupational burnout, emotional exhaustion, desensitization, and personal achievement and work performance, and in summary, a negative relationship was seen between occupational burnout and job performance in football referees.